Using complex network analysis to assess the evolution of international economic integration: The cases of East Asia and Latin America - Javier Reyes; Stefano Schiavo; Giorgio Fagiolo (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2007)
Over the past four decades the High Performing Asian Economies (HPAE) have followed a development strategy based on the exposure of their local markets to the presence of foreign competition and on an outward oriented production. In contrast, Latin American Economies (LATAM) began taking steps in this direction only in the late eighties and early nineties, but before this period these countries were more focused in the implementation of import substitution policies. These divergent paths have led to sharply different growth performance in the two regions. Yet, standard trade openness indicators fall short of portraying the peculiarity of the Asian experience, and to explain why other emerging markets with similar characteristics have been less successful over the last 25 years. This paper offers an alternative perspective on the issue by exploiting recently-developed indicators based on weighted network analysis. This allows us to investigate the whole structure of international trade relationships and to determine both the position of HPAE countries in the network and its evolution over time. We show that HPAE countries are more integrated into the world economy, as they have moved over the past 25 years from the periphery of the network towards its core. In contrast, the LATAM region seems to be loosing presence within the network or, at best, its integration process has remained stagnant.
Keywords: F10; D85; 330; International trade; High Performing Asian Economies; Latin American Economies; Development; Growth; Networks; Complex Weighted Networks; World Trade Web; Centrality